Strategic Planning for Technological Innovation in Canadian Post Secondary Education - Stockley, Denise (Canadian Journal of Learning and Technology, 2004)
In this study, institution-wide strategic plans that were available online were examined in detail to determine how educational technology was referred to in these documents. Based on this data and the literature, a schedule of principles for supporting the implementation of educational technology in post-secondary teaching was developed. Institutions that are formatively evaluating local efforts to understand and improve technologically supported instruction can use this checklist diagnostically.